Reinforcement of concrete with fibroconcrete - Pulatova Zukhra Umetovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The use of fiber concrete reduces the total cost of construction work. The thickness of the concrete layer can be reduced to half the layer compared to conventional concrete.